The work and social adjustment scale: Reliability, sensitivity and value. (June 2014) - Zahra, Daniel; Qureshi, Adam; Henley, William; Taylor, Rod; Quinn, Cath; Pooler, Jill; Hardy, Gillian; Newbold, Alexandra; Byng, Richard
Abstract Objective. To investigate the psychometric properties of the Work and Social Adjustment Scale (WSAS) as an outcome measure for the Improving Access to Psychological Therapy programme, assessing its value as an addition to the Patient Health (PHQ-9) and Generalised Anxiety Disorder questionnaires (GAD-7). Little research has investigated these properties to date. Methods. Reliability and responsiveness to change were assessed using data from 4, 835 patients. Principal components analysis was used to determine whether the WSAS measures a factor distinct from the PHQ-9 and GAD-7. Results. The WSAS measures a distinct social functioning factor, has high internal reliability, and is sensitive to treatment effects. Conclusions. The WSAS, PHQ-9 and GAD-7 perform comparably on measures of reliability and sensitivity. The WSAS also measures a distinct social functioning component suggesting it has potential as an additional outcome measure.